Predictors and Interrelationship of Patient‐Reported Outcomes in Antiphospholipid Syndrome: A Cross‐Sectional Study - Julia K. Weiner; Tristin Smith; Claire K. Hoy; Cyrus Sarosh; Jacqueline A. Madison; Amala Ambati; Ajay Tambralli; Noah Peters; Corinne Packel; Kelsey Gockman; Yu Zuo; Emily M. Briceño; et al. (ACR Open Rheumatology, 2023)
Objective This study assessed patient‐reported outcomes (PROs) in individuals with persistently positive antiphospholipid antibodies (aPL) to better understand how living with aPL may affect their quality of life. Methods Patients completed Patient‐Reported Outcomes Measurement Information System Physical Function (PF) and Cognitive Function (CF) Short Forms as well as the pain intensity (PI) rating (scale of 1‐10). Patients were characterized for demographics, clinical manifestations of antiphospholipid syndrome (APS), cardiovascular risk factors, laboratory test results, and medication usage. Multivariate modeling was done via linear regression. Results Of 139 patients, 89 had primary APS, 21 had secondary APS, and 29 had persistent aPL without meeting clinical criteria for APS. The average T scores (±SD) for PF and CF were 45.4 ± 9.2 and 48.6 ± 11.6, respectively; the average for PI was 3.0 ± 2.6. Approximately half of the patients (47%) endorsed at least mild impairment in PF (T score < 45). Mean PF, CF, and PI did not differ between diagnostic groups. Individuals who endorsed more impairment on one measure also tended to endorse more impairment on another (Pearson r = 0.43‐0.59). In the multivariate models, age, smoking, pain medications, and serotonergic medications were associated with impairment in at least one PRO domain. The Damage Index for APS was significantly correlated with both PF and CF. Conclusion Individuals living with APS endorsed more impairment in PF (and potentially CF) than expected for the general population. The relationship between certain medications and PROs warrants further study, as does the longitudinal trajectory of these and other PROs.